Perdagangan Berjangka Komoditi : Berdzikirlah dengan Physical Delivery - Tutuko, Bambang (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Commodity Futures Trading in Indonesia is administered by the government under the auspices of the Commodity Futures Trading Supervisory Agency (BAPPEBTI) with the aim of establishing the price of primary commodities (price discovery) and as a hedging facility using futures contracts. However, current futures trading is only a means of speculation caused by its specifications and transaction mechanism.The application of the three principles of dhikr: the principle of harmony, the principle of integrity, and the principle of one on the quest for hedging solutions in commodity futures will lead to trade where the parties who transact share the risk (risk sharing). Risk sharing can only occur if there is a common goal between buyers and sellers to manage risk (the principle of the one-an). The similarity of objectives will result in a commitment between buyers and sellers to perform physical handover backed by regulation to create a liquid market (the principle of harmony), so that the wholeness of trade mechanisms involving market participants, markets, and regulators will be maintained. The integrity of the role of the stakeholders of commodity trading is what will lead to the solution of the hedge without having to separate the risk with its trading activities (principle of wholeness).The